Penurunan Kemiskinan dan Terwujudnya Pembangunan Berkelanjutan di Pesisir Kota Surabaya Sebagai Optimalisasi Ekonomi Biru - Sofa, Devi Maya; Mardianto, Totok; Djenal, Michael Oswald Kritiano (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study analyzes the potential of the blue economy in reducing poverty and achieving sustainable development in the coastal areas of Surabaya. Using mixed methods with an exploratory sequential design in three coastal villages (Kedung Cowek, Kenjeran, and Sukolilo Baru), the study involved four key informants and 85 fisherman respondents. The results show that the coastal areas of Surabaya have diverse blue economy potential, including capture fisheries, aquaculture, marine product processing, and marine tourism. Quantitative analysis proves that blue economy optimization has a significant effect on poverty reduction (R² = 0.476) and sustainable development (R² = 0.322). However, its implementation is constrained by fluctuations in fishermen's income, low financial literacy, and the incompatibility of assistance programs. A sustainable development model requires the integration of business diversification, institutional strengthening, and a transformation of the community's mindset through multi-stakeholder collaboration to create a sustainable blue economy ecosystem.